Effect on Different Amount of TiO2 P25 powder for Dye-Sensitized Solar Cell application - Fakhriah, R.; Ahmad, M. K.; Hamed, N. A. F.; Ahmad, N.; Fahrizal, F. N.; Mohamad, F.; Nafarizal, N.; Soon, C. F.; Ameruddin, A. S.; Faridah, A. B.; Shimomura, M.; Murakami, K. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
Titanium Dioxide (TiO2) has been successfully prepared using the spray pyrolysis method. Then it was optimized by conducting several repetition procedures and deposited on fluorine tin oxide (FTO) substrate. The amount of TiO2 P25 was varied from 0.1 grams (g) to 0.5 g in order to study the exact amount of TiO2 P25 needed to produce the highest efficiency solar cell result. All the thin films were annealed at fixed temperature at 500oC within 3 hours. The thickness of the thin film was measured through a surface profiler. From the measurement, it can be concluded that the utilization of different amount of TiO2 P25 affects the thickness of thin film. The properties of TiO 2 thin film were investigated by Field Emission Scanning Electron Microscopy (FE-SEM), X-ray Diffraction (XRD) and Four Point Probes. The amount of TiO2 P25 shows the notable effect on morphological and structural of deposit-TiO2. The optimum porosity of thin film was observed when 0.3g of TiO2 P25 has been used while XRD patterns exhibit anatase and rutile structures based on the peak existed. The adsorption of dye molecules increased when the thickness of thin film increased due to the increase in crystal size. Hence, it improves the short circuit density respectively. The efficiency of Dye-Sensitized Solar Cell increased as short circuit density and film thickness increased. Based on this research, the amount of 0.3g TiO2 P25 with thickness 17.89 µm can be used in DyeSensitized Solar Cell applications with the optimum power conversion efficiency measured by solar simulator which is 1.84%.